2007
DOI: 10.1002/pssa.200674325
|View full text |Cite
|
Sign up to set email alerts
|

Macropore growth in a prepatterned p‐type silicon wafer

Abstract: The formation process of ordered macropores in a prepatterned p‐type silicon wafer was investigated. FE‐SEM observation focusing on the early stage of the pore growth clarified the two‐step process of macropore formation, whose first step was isotropic pore expansion from prepared etch pits and the second was anisotropic growth in the depth direction. Investigation using different etch‐pit patterns revealed that ordered macropores with constant diameters were obtained when the spacing of etch pits was 3–8 μm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
0
9
2
Order By: Relevance
“…The thickness of a nanorod remains constant and a pore is grown only in the depth direction. 13) Figure 6 shows the SEM images of the nanorod array with an approximately 350 nm diameter formed in p-type silicon when two-step currents (40 mA, 200 s + 38 mA, 1600 s) are applied in order to further reduce significantly the diameter of a nanorod using the same etch-pit mask pattern shown in Fig. 1(c).…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of a nanorod remains constant and a pore is grown only in the depth direction. 13) Figure 6 shows the SEM images of the nanorod array with an approximately 350 nm diameter formed in p-type silicon when two-step currents (40 mA, 200 s + 38 mA, 1600 s) are applied in order to further reduce significantly the diameter of a nanorod using the same etch-pit mask pattern shown in Fig. 1(c).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison with the previous work.-We reported that ordered macropore formation is strongly based upon the interval of pre-etch pits. 13 Using substrates patterned with 8, 5, and 3 m intervals, ordered macropores were formed, while with 2 m, disordered macropores were obtained at 13 mA cm −2 . One of the important insights to understand the effect of the prepattern interval on ordered macropore formation is highlighted based on the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study on the formation of ordered macropores starting from pre-etched substrates having different intervals revealed that ordered macropores were obtained when the intervals between pre-etch pits were 3, 5, and 8 m, while pore walls collapsed, and ordered macropores were not obtained with a 2 m interval wafer. 13 The diameter and wall thickness of the ordered macropores showed a tendency to decrease with a decrease in the interval of pre-etch pits, which could not be explained by considering the width of the space-charge region. 7 In the previous experiment, the size of the etch pits was kept constant, while the interval of the pre-etch pits was varied.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Particularly, the fabricated PSi films/layers via the galvanostatic approach are often produced by the electrochemical etching of silicon in hydrofluoric acid-based electrolyte mixed with some surfactant like ethanol, and the starting silicon wafer is a single crystalline substrate, which would lead to the formation of various pore arrays with nano/microporous silicon features [7][8][9][10][11][12]. Such a wide range of pore sizes and morphologies was reported to be dependent greatly on the electrolyte concentration of fluoride ions, solution pH, the applied anodic current intensity, the use of organic additives, operating temperature, the silicon wafer characteristics (p-type or n-type silicon with crustal orientation) and whether the electrochemical anodization is being conducted in the dark or under the illumination [13,14]. In addition to this, the etching time was found to be the main factor to control and determine the produced pore length (the thickness of PSi layer).…”
Section: Introductionmentioning
confidence: 99%